Cephalometric norms for Bimaxillary Protrusion in Trinidad and Tobago: a preliminary study. Issue 2 (28th September 2020) - Hoyte, Trudee; Ali, Anil; Mossey, Peter
ABSTRACT: Abstract: The aim of this study is to establish for the first time cephalometric norms for bimaxillary protrusion in Trinidad and Tobago population and to compare findings to previously published norms for other bimaxillary protrusion groups. Materials and Methods: In total, 109 standardized lateral cephalometric radiographs were taken by one investigator of bimaxillary protrusion patients prior to receiving orthodontic treatment. The sample consisted of 52 boys and 57 girls aged 10–17 years. The cephalograms were traced using 48 hard and soft tissue and 25 linear and angular cephalometric measurements. Independent sample t-test was used to assess inter-gender differences, norms were calculated. The results were then compared to the norms for other bimaxillary protrusion populations. Results: The mean values and standard deviations obtained were: SNA, 85.9° (± 4.9°); SNB, 78.7°(± 4.5°); ANB, 7.2°(± 2.5°); MMPA, 32.3°(±5.1°); UI-LI, 109.7° (±8.2°); UI-Max, 118.7° (±6.1°); LI-Man, 101.4° (±5.9°); LI-Apo, 3.8° (±2.6°); Upper lip to E-plane 2.0 mm (±3) and Lower Lip to E-plane 5.6 mm (±3.2).The independent t-test showed sexual dimorphism with SNA and upper and lower lip to E-plane being higher in males compared to females. The maxilla and mandible were more anteriorly placed in this sample as compared to Caucasian norms. ANB, MMPA, UI-Max, LI-Man, LI-Apo, upper lip and lower lip to E-plane, were all higher in this population compared to other bimaxillary protrusion populations. Conclusions: There are some fundamental differences in the cephalometric norms for the bimaxillary protrusion population in Trinidad and Tobago and in the context of orthodontic diagnosis and treatment planning these cephalometric norms should be the yardstick.